2012
DOI: 10.1007/s00203-012-0826-x
|View full text |Cite
|
Sign up to set email alerts
|

Specific PCR-based detection of Alternaria helianthi: the cause of blight and leaf spot in sunflower

Abstract: Alternaria helianthi is an important seed-borne pathogenic fungus responsible for blight disease in sunflower. The current detection methods, which are based on culture and morphological identification, are time-consuming, laborious and are not always reliable. A PCR-based diagnostic method was developed with species-specific primers designed based on the sequence data of a region consisting of the 5.8S RNA gene and internal transcribed spacers-ITS 1 and ITS 2 of nuclear ribosomal RNA gene (rDNA) repeats of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Since its development in the 1990s, real-time PCR has emerged as a reliable and sensitive method for detecting and quantifying phytopathogenic and antagonistic fungi (Schena et al 2004), and represents a highly sensitive and specific technique for the detection and quantification of nucleic acids (Tylor et al 2001). Protocols for the qualitative recognition of Alternaria species in sunflowers and foodstuff have recently been established (Pavón et al 2012;Udayashankar et al 2012). Quantitative detection of A. alternata in tomato has been developed by Schuhegger et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since its development in the 1990s, real-time PCR has emerged as a reliable and sensitive method for detecting and quantifying phytopathogenic and antagonistic fungi (Schena et al 2004), and represents a highly sensitive and specific technique for the detection and quantification of nucleic acids (Tylor et al 2001). Protocols for the qualitative recognition of Alternaria species in sunflowers and foodstuff have recently been established (Pavón et al 2012;Udayashankar et al 2012). Quantitative detection of A. alternata in tomato has been developed by Schuhegger et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…The ITS regions of ribosomal RNA often contains pathogen specific conserved sequences that enable designing of genera and species consensus primers (White et al 1990;Xue et al 1992). Also the high copy numbers of rRNA genes in a fungal genome serve as an (Jasalavich et al 1995;Kusaba and Tsuge 1995;Pavlina et al 2002;Udayashankar et al 2012). In the present instance, primers specificto-conserved as well as the unique sequences in the ITS2 region of rRNA of A. helianthi were used to develop the assay.…”
Section: Discussionmentioning
confidence: 97%
“…Healthy sunflower seeds were artificially infected by the method described by Udayashankar et al (2012) and observed under the stereo microscope for the presence of mycelial and conidial growth of A. helianthi after 8 days of incubation at 22±2°C under alternating 12 h periods of darkness and near ultraviolet (NUV) light.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations